Competition, Decentralization, and Candidate Selection in Mexico. (June 2016) - Bruhn, Kathleen; Wuhs, Steven
This article examines how political context affects the strategic choice of nomination rules, using data from federal and state-level legislative elections. Our analysis indicates that competition affects the selection rules parties adopt. Overall, parties are most likely to use open selection rules when they think they will win, largely due to the effects of activist competition over coveted nominations. However, state-level party leaders have not been consistently empowered by decentralization. Although state-level party leaders do have nonnegligible influence when it comes to the selection of local legislative nominees, they have more influence in those states that are the most dependent on the federal government for resources. Competitive context continues to be a stronger predictor of selection rule choice than decentralization.